Language Investment during University Adjustment: The Divergent Path of Two International Chinese Freshmen. Issue 4 (3rd July 2020) - Crowther, Dustin
ABSTRACT: International students encounter academic and social adjustments different than those of their domestic peers. Of particular concern is language proficiency, specifically students' investment in continual language development throughout university study. In the current article, I present a comparative case study of two Chinese freshmen (Jenn, Angela) completing university study in the United States. Each participant completed seven individual, 60-minute interviews over the course of their first year of study. Through an analysis of narrative approach, I establish a complex interaction between Jenn's and Angela's past (U.S. high school study abroad) and current (university) academic and cultural experiences and future expectations (professional goals). Jenn's perception of high school belonging led to high integration into the university community. Angela's perception of rejection by her American peers strengthened her connection to the local Chinese community. This contrast in communal acceptance fostered opposing levels of language investment, with only Jenn intent on pursuing further opportunities in the target community.